Factors Affecting Students’ Attendance in English Language Programs A Case Study at Two English Language Institutions in Indonesia - Nur Endah, Dian; Duwi Purwandari, Junita; Abduh Almanar, Muhammad (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study explores the factors influencing attendance among employees enrolled in English language courses, with a focus on understanding attendance patterns and proposing interventions to improve participation. English proficiency is a critical asset in the global era, and many companies in Indonesia offer English courses as part of their professional development programs. Despite their importance, these programs face attendance challenges due to factors such as professional commitments and schedule conflicts. The research employs a quantitative method, utilizing surveys to gather data from 15 employees participating in English courses at two institutions in Indonesia, one in Jakarta (called Bravo – pseudonym) and another one in Bandung (called Delta – pseudonym). Results highlight two primary factors affecting attendance: (1) professional development as a key motivator and (2) schedule conflicts as a major barrier. To address these challenges, the study proposes actionable interventions, by implementing a blended learning model and integrating mutual agreements between companies and course providers including creating supportive environment such as implementing blended learning model, designating learning hours and providing reward or incentive.